Toddalia asiatica (Linn.) Lam. – A Comprehensive Review - Rajkumar, Molmoori; Chandra, Rodda Harish; Asres, Kaleab; Veeresham, Ciddi (Pharmacognosy Reviews)
Toddalia asiatica (Lopez root): Rutaceae, a woody liana, is used traditionally in the treatment of malaria, sprains, cough, fever, neuralgia, epilepsy, dyspepsia and other disease conditions. Extracts of the plant have been reported to have anticancer, antiHIV, antimicrobial, antifeedant activities. A wide range of chemical constituents such as benzophenanthridine alkaloids, coumarins, cyclohexylamides and terpenoids have been isolated especially from the root bark of the plant. This review gives insight into the detailed profile of the traditional uses, chemical constituents, biological and pharmacological actions of the plant.
Keywords: Toddalia asiatica; Chemistry; Biological and Pharmacological activities